The Relationship of Children Driven to Crime with Place of Residence, Crime Scene and Type of Crime: The Sample of 2nd Juvenile Court of İstanbul Court House - Gülüm, Zeynep; Cohen, Zeynep Pınar; Demircan, Yusuf Tunç (The Bulletin of Legal Medicine, 2017)
Objective: Studies of children’s residences has gained importance depending on the fact that environmental risk factors are more significant than individual risk factors in juvenile delinquency. This research aims to determine the settlements where children intensively driven to crime, identify typical type of crime in these neighborhoods and reveal the relationship between the places where the child is living and driven to crime. With the results of this study, it is aimed to shed light on the prevention studies that must be conducted in the neighborhoods where children intensively driven to crime. Methods: In this study, 520 justified decisions, finalized in 2015 about 668 children driven to crime, that were reached from the second juvenile court of İstanbul Courthouse were examined. Descriptive analysis was used in order to determine frequency and percentage distribution of the data and chi-square test was used to assess the interrelatedness of categorical variables. Results: Of subjects, 90% were male and 76.5% were in the 15-18 age range. When the distribution of the type of crime was examined, crime against property (62%) seemed to be more intensive. In terms of the distribution of crime scene, it was observed that Fatih (27.5%), Şişli (19.3%) and Beyoğlu (15.3%) districts come forward. In the sequence of districts where children driven to crime resided Fatih (19%) came in the first place again, afterwards Beyoğlu (13.5%), Kağıthane (11.4%) and Eyüp (9.7%) districts came. Nevertheless, when examined on the basis of the neighborhood, İstiklal Neighborhood, which located in Beyoğlu district, came first. By the result of chi-square tests, it was observed that the relations between type of crime and crime scene, place of residence and crime scene, type of crime and place of residence were statistically significant. Conclusion: By assessing crime scene, type of crime and place of residence together, the study showed that Fatih district came first at all of these variables. When examined at the level of residential neighborhood, it was revealed that in some neighborhoods, a particular type of crime has been specialized.